2013
DOI: 10.9738/cc171.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Natural and Recombinant Hirudin on VEGF Expression and Random Skin Flap Survival in a Venous Congested Rat Model

Abstract: We aim to investigate the effects of locally injected natural and recombinant hirudin on vascular endothelial growth factor (VEGF) expression and flap survival in venous congested skin flaps using a rat model. A dorsal random skin flap (10 3 3 cm) was prepared on each of 30 Wistar rats to establish a venous congested model. The rats were randomly divided into 2 treatment groups [receiving subcutaneous injection of either natural hirudin (6 U) or recombinant hirudin (6 U)] and a control group, which received su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…VEGF has well-established functions, including stimulating proliferation of endothelial cells and promoting ischemic flap revascularization, that lead to improved flap survival. [17][18][19] Our previous study also showed that Traditional Chinese Medicines, such as Muscone, have positive effects to promote the survival of random skin flap as well as enhance the expression of VEGF. 20 In this study, the expression of VEGF in salidroside-treated flaps was markedly higher, compared with the control group, both in terms of immunohistochemical staining and Western blot.…”
Section: Discussionmentioning
confidence: 94%
“…VEGF has well-established functions, including stimulating proliferation of endothelial cells and promoting ischemic flap revascularization, that lead to improved flap survival. [17][18][19] Our previous study also showed that Traditional Chinese Medicines, such as Muscone, have positive effects to promote the survival of random skin flap as well as enhance the expression of VEGF. 20 In this study, the expression of VEGF in salidroside-treated flaps was markedly higher, compared with the control group, both in terms of immunohistochemical staining and Western blot.…”
Section: Discussionmentioning
confidence: 94%
“…56) Increased VEGF expression showed improved microvascular perfusion and enhanced neovascularization in skin flap surgeries. 39,56,57) It has been reported that therapeutic potentials of natural antioxidant epigallocatechin gallate on flap survival by inducing VEGF expression. 39) On the other hand, same compound inhibits pathological VEGF in cancerous tissue.…”
Section: Fig 4 Regional Blood Perfusion In the Skin Flapsmentioning
confidence: 99%
“…If this cannot be treated effectively, flap necrosis is likely to occur. Venous congestion leads to skin swelling and purple discoloration (26). According to the present study, the area of swollen skin in the experimental groups was significantly less than in the control group (by general observation).…”
Section: Discussionmentioning
confidence: 68%
“…DG may potentially improve flap survival via various mechanisms. It has been reported that venous crisis is more common than arterial crisis following flap surgery (26). If this cannot be treated effectively, flap necrosis is likely to occur.…”
Section: Discussionmentioning
confidence: 99%